2012
DOI: 10.5812/iranjradiol.8444
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Panoramic and Lateral Cephalometric Radiographs for Measuring the Gonial Angle

Abstract: BackgroundThe gonial angle is one of the most important measurements required for orthodontic treatment and orthognathic surgery. It is difficult to determine the accurate measurement of each gonial angle on cephalometric radiographs because of superimposition of the left and right angles.ObjectivesThe aim of the present study was to determine the right and left gonial angles on panoramic radiographs and to compare them with an evaluated cephalometric sample.Patients and MethodsA total of 80 panoramic and 80 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 14 publications
4
25
1
5
Order By: Relevance
“…Despite analyzing the GA through radiographies, our findings agreed with those presented by Oksayan et al [23], Zangouei-Booshehri et al [25] and Joo et al [29] that did not find differences between the right and the left sides. In the study by Yanikoglu and Yilmaz [20], differences in angle values between the right and left sides in patients from 40 to 70 years of age were reported; however, it is worth mentioning that this patient sample had periodontal impairment.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Despite analyzing the GA through radiographies, our findings agreed with those presented by Oksayan et al [23], Zangouei-Booshehri et al [25] and Joo et al [29] that did not find differences between the right and the left sides. In the study by Yanikoglu and Yilmaz [20], differences in angle values between the right and left sides in patients from 40 to 70 years of age were reported; however, it is worth mentioning that this patient sample had periodontal impairment.…”
Section: Discussionsupporting
confidence: 80%
“…Although we did not find similar studies related with age and occlusion relationships in the literature, we verified that in the study by Oksayan et al [23], which was performed in individuals with an average age of 17 years, and in that by ZangoueiBooshehri et al [25], with children aged 6 to 12 years, no differences in GA values were found between the sexes, when both evaluated three sagittal relationships. In contrast from these findings, Xie et al [28] found statistically significant differences for angle values between men and women, in groups with average age of 27 and 64 years.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Many studies have evaluated the GA on PR, but no previous report described how to produce accurate, detailed images of the GA (9,11,(12)(13)(14)(15)(16)(17)(18)(19)(20). It is essential to develop a detailed method for drawing the inferior border of the mandible-in which only one line is made on the inferior border of the mandible-so as to not change the condition of the GA. Additionally, if the GA on PR is anatomically similar to the GA on LCR or has a characteristic structure, PR may prove to be more useful and could become a high-value-added dental examination.…”
Section: Introductionmentioning
confidence: 99%